2023
DOI: 10.1136/bjsports-2022-106436
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of concussion following COVID-19 infection in high school athletes

Abstract: ObjectiveTo compare concussion rates (CRs) over one academic year in high school athletes with and without a COVID-19 infection prior to concussion.MethodsIllness and concussion were prospectively reported for male and female high school athletes across six states over one academic year in the Players Health Rehab surveillance system. Concussion was truncated to 60 days following recovery and return to sport from COVID-19. CRs were estimated per 1000 athletes per academic year and stratified by those who teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The link between the incidence of concussions and COVID-19 infections is outside the scope of this study; however, this was also recently observed in a cohort of high school athletes. 34 This study suffers from limitations because of the relatively small sample of participants; however, it contributes to filling the knowledge gap about concussions in female athletes. 35 In the 2020 to 2021 season, most international competitions were cancelled because of the COVID-19 pandemic, and the low prevalence observed should be considered with this context in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between the incidence of concussions and COVID-19 infections is outside the scope of this study; however, this was also recently observed in a cohort of high school athletes. 34 This study suffers from limitations because of the relatively small sample of participants; however, it contributes to filling the knowledge gap about concussions in female athletes. 35 In the 2020 to 2021 season, most international competitions were cancelled because of the COVID-19 pandemic, and the low prevalence observed should be considered with this context in mind.…”
Section: Discussionmentioning
confidence: 99%
“…The link between the incidence of concussions and COVID-19 infections is outside the scope of this study; however, this was also recently observed in a cohort of high school athletes. 34…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, neurological symptoms seen in individuals with post-concussive syndrome (PCS) are strikingly similar to neurological symptoms occurring in COVID-19, either in acute or long COVID cases, and include headaches, dizziness, and problems with concentration and memory [87]. A recent study by Bullock and collaborators [88] showed that high school athletes who had an active COVID-19 infection were three times more likely to sustain a concussion. This may be due to deconditioning because of reduced training habits during illness but could also potentially be due to parallel pathophysiological events in the brain.…”
Section: Increased Vulnerability In Patients With Traumatic Brain Inj...mentioning
confidence: 94%